2017
DOI: 10.1002/cssc.201701674
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Photoelectrochemical Applications of Silicon Materials for Solar‐to‐Chemicals Conversion

Abstract: Photoelectrochemical (PEC) technology for the conversion of solar energy into chemicals requires cost-effective photoelectrodes to efficiently and stably drive anodic and/or cathodic half-reactions to complete the overall reactions for storing solar energy in chemical bonds. The shared properties among semiconducting photoelectrodes and photovoltaic (PV) materials are light absorption, charge separation, and charge transfer. Earth-abundant silicon materials have been widely applied in the PV industry, and have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 139 publications
0
66
0
Order By: Relevance
“…An efficiency analysis of these dual semiconductor systems has demonstrated that the optimal bandgap is ≈1–1.4 eV for the bottom absorber and ≈1.7–2.1 eV for the top absorber 1–3. Among semiconductors that exhibit an adequate bandgap, silicon (bandgap of 1.1 eV) has emerged as a promising choice due to its earth‐abundance and wide‐spread use in the electronics and solar cell industry 4–8. A common strategy to obtain high photovoltage with Si has been to fabricate traditional p–n Si homojunctions 9–13.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An efficiency analysis of these dual semiconductor systems has demonstrated that the optimal bandgap is ≈1–1.4 eV for the bottom absorber and ≈1.7–2.1 eV for the top absorber 1–3. Among semiconductors that exhibit an adequate bandgap, silicon (bandgap of 1.1 eV) has emerged as a promising choice due to its earth‐abundance and wide‐spread use in the electronics and solar cell industry 4–8. A common strategy to obtain high photovoltage with Si has been to fabricate traditional p–n Si homojunctions 9–13.…”
Section: Introductionmentioning
confidence: 99%
“…
and solar cell industry. [4][5][6][7][8] A common strategy to obtain high photovoltage with Si has been to fabricate traditional p-n Si homojunctions. [9][10][11][12][13] Furthermore, significant effort has been focused on improving catalytic activity [14][15][16][17][18] of electrocatalysts attached to Si and increasing solar utilization by nanostructuring Si and/or introducing plasmonic materials.
…”
mentioning
confidence: 99%
“…In addition, it has a suitable bandgap (ca. 1.1 eV) for sunlight harvesting, and a long carrier diffusion length for facile charge transport compared with metal oxide semiconductors . Nevertheless, n‐Si based photoanodes suffer from low photovoltage, sluggish oxygen evolution reaction (OER) as well as severe corrosion when exposed to aqueous electrolyte, limiting their practical application for photoelectrochemical (PEC) water oxidation …”
Section: Introductionmentioning
confidence: 99%
“…1.1 eV) for sunlight harvesting, and a long carrier diffusion length for facile charge transport compared with metal oxide semiconductors. [2,3] Nevertheless, n-Si based photoanodes suffer from low photovoltage, sluggish oxygen evolution reaction (OER) as well as severe corrosion when exposed to aqueous electrolyte, limiting their practical application for photoelectrochemical (PEC) water oxidation. [4][5][6] Many efforts have been devoted to stabilize Si photoelectrodes by employing chemically stable materials as corrosion-resistant protection layers, such as doped SiO x , transparent conductive www.advancedsciencenews.com www.small-methods.com in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with planar Si, nanoporous black Si exhibits many attractive properties, such as low reflectance and high surface area. [14,15] Recently, nanoporous black Si has shown excellent PEC activity resulting from robust light absorption efficiency and charge transport properties. [16][17][18][19] Unfortunately, Sibased photoelectrodes often suffer from poor stability due to spontaneous silicon oxide (SiO 2 ) forma tion upon exposure to air.…”
mentioning
confidence: 99%